2016
DOI: 10.5792/ksrr.2016.28.2.99
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Medial Patellofemoral Ligament Reconstruction Combined with Tibial Tuberosity Transfer in the Treatment of Patellofemoral Instability

Abstract: A systematic review of the literature was undertaken to evaluate the efficacy of medial patellofemoral ligament (MPFL) reconstruction combined with tibial tuberosity transfer (TTT) in the treatment of patellofemoral instability. Using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, a systematic search was carried out to identify and review the published literature pertinent to MFPL reconstruction combined with TTT. Relevant studies were critically appraised with narrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…[1][2][3][4]14,17,22,75 Whereas some authors have found good clinical outcomes and low redislocation rates after isolated MPFL reconstruction even in the presence of ARFs, 24,49,51,60,76 other authors have found a correlation between ARFs and unsatisfactory outcomes and failure after MPFL reconstruction. k Therefore, additional stabilization procedures are increasingly performed in combination with MPFL reconstruction, such as trochleoplasty, 5,6,10,34,54 medialization or distalization of the tibial tuberosity, 12,26,44,50 and osteotomies to correct torsion and/or valgus malalignment. [19][20][21][22][23]27,28,55 The results of the current study suggest that the presence of ARFs is related to failure after MPFL reconstruction, as only 15% of patients had no ARFs, whereas 2 or more ARFs were observed in 65% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4]14,17,22,75 Whereas some authors have found good clinical outcomes and low redislocation rates after isolated MPFL reconstruction even in the presence of ARFs, 24,49,51,60,76 other authors have found a correlation between ARFs and unsatisfactory outcomes and failure after MPFL reconstruction. k Therefore, additional stabilization procedures are increasingly performed in combination with MPFL reconstruction, such as trochleoplasty, 5,6,10,34,54 medialization or distalization of the tibial tuberosity, 12,26,44,50 and osteotomies to correct torsion and/or valgus malalignment. [19][20][21][22][23]27,28,55 The results of the current study suggest that the presence of ARFs is related to failure after MPFL reconstruction, as only 15% of patients had no ARFs, whereas 2 or more ARFs were observed in 65% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A tibial tubercle osteotomy (TTO) may also be performed, often in combination with MPFL reconstruction, especially in those with patella alta [17]. Case series have suggested good outcomes for MPFL reconstruction, alone or combined with tubercle osteotomy approaches [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…45 Current guidelines on the treatment of patellar instability associated with patella alta recommend MPFL reconstruction (MPFLr) and tibial tuberosity distalization to better stabilize the patella. 6,9,21 The overall reported complication rate of tibial tubercle transfer is 7.4% (eg, proximal tibial fractures, tibial tuberosity nonunion, skin necrosis), and about 50% of these patients require hardware removal. 18,34,41 On the other hand, some preliminary studies reported a slight decrease in patellar height in the postoperative…”
mentioning
confidence: 99%